GENE-06. EXPRESSION OF LINC00152, A PUTATIVE SPONGE FOR TUMOR-SUPPRESSIVE micro-RNA, CORRELATES WITH GLIOMA GRADE. Issue 11 (6th November 2017) - Mueller, Soeren; He, Daniel; Hayes, Josie; Liu, Siyuan; Malatesta, Martina; Kriegstein, Arnold; Aghi, Manish; Lim, Daniel; Diaz, Aaron
Abstract: Long noncoding RNAs (lncRNAs) play crucial roles in normal physiology as well as various disease states. We compared The Cancer Genome Atlas (TCGA) lower grade glioma (LGG, n=414) and glioblastoma (GBM, n=144) RNA-seq data and found only a few differentially expressed lncRNAs. The most significantly differentially expressed lncRNA was LINC00152. In an independent cohort (n=109 grade II, n=72 grade III, n=144 grade IV) LINC00152 expression was enriched in tumors with higher grade. In LGG, LINC00152 levels were negatively correlated with methylation of its promoter region (r=-0.69, p < 2.2e-16) and silencing was confirmed in single cell RNA-seq of 10 astrocytoma and 6 oligodendroglioma patients, where less than 0.3% of malignant cells express LINC00152. Furthermore, expression of LINC00152 was increased in IDH1 wild-type immortalized human astrocytes compared to astrocytes transfected with mutant IDH1, suggesting an association between LINC00152 promoter methylation and IDH1 mutation in primary LGG. Interestingly, comparing LINC00152 expression between matched primary and recurrent IDH1 mutant gliomas (n=53), we found significantly elevated expression in recurrent tumors (adj. p<9e-7). In glioblastoma, LINC00152 expression was significantly higher in mesenchymal compared to proneural GBMs (adj. p<0.01). In single cell RNA-seq of GBM biopsies of 7 patients, more than 60% of malignant single cells were positive for LINC00152 expression. Co-expression network analysis revealed a strong co-expression of LINC00152 with glioma cell proliferation markers. Furthermore, bioinformatic prediction of miRNA binding sites suggests that LINC00152 may act as a miRNA sponge for 20 miRNAs, 17 of which have been shown to be tumor suppressor miRNAs in glioma (ex. let-7, miR-153, miR-216).